More than words: Neurophysiological correlates of semantic dissimilarity depend on comprehension of the speech narrative. (15th September 2022) - Broderick, Michael P.; Zuk, Nathaniel J.; Anderson, Andrew J.; Lalor, Edmund C.
Abstract: Speech comprehension relies on the ability to understand words within a coherent context. Recent studies have attempted to obtain electrophysiological indices of this process by modelling how brain activity is affected by a word's semantic dissimilarity to preceding words. Although the resulting indices appear robust and are strongly modulated by attention, it remains possible that, rather than capturing the contextual understanding of words, they may actually reflect word‐to‐word changes in semantic content without the need for a narrative‐level understanding on the part of the listener. To test this, we recorded electroencephalography from subjects who listened to speech presented in either its original, narrative form, or after scrambling the word order by varying amounts. This manipulation affected the ability of subjects to comprehend the speech narrative but not the ability to recognise individual words. Neural indices of semantic understanding and low‐level acoustic processing were derived for each scrambling condition using the temporal response function. Signatures of semantic processing were observed when speech was unscrambled or minimally scrambled and subjects understood the speech. The same markers were absent for higher scrambling levels as speech comprehension dropped. In contrast, word recognition remained high and neural measures related to envelope tracking did not vary significantly across scrambling conditions. This supports the previous claim that electrophysiological indices based on the semantic dissimilarity of words to their context reflect a listener's understanding of those words relative to that context. It also highlights the relative insensitivity of neural measures of low‐level speech processing to speech comprehension. Abstract : 128‐channel EEG was recorded from subjects who listened to an audiobook presented in its original, narrative form, or after scrambling the word order by varying amounts. The EEG was regressed against a train of impulses reflecting the 'semantic dissimilarity' of each word to its preceding context. This resulting 'temporal response function' reflected the fact that the subjects understood the narrative when the story was presented in its original form, but not after scrambling the word order.